THE INFLUENCE OF WORK FACILITIES, JOB PLACEMENT, AND WORK PRESSURE ON PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE IN THE WORK UNIT OF SPECIAL ANTI-TERROR DETACHMENT 88 AT POLRI MABES - Maulana, Ervindo; Satriawan, Bambang; Khaddafi, Muammar; Titik Windayati, Diana; Fatahurrazak, Fatahurrazak (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Every organization is often faced with problems regarding the performance of its personnel. Every leader in a work unit will always try to ensure that every activity carried out achieves maximum results and is carried out effectively and efficiently. In order to achieve the desired level of effectiveness and efficiency, the work unit must have a good work system or have good performance. Therefore, the performance of personnel is very dependent on the good or bad performance of the organization. Where the performance of an organization depends on the performance of its personnel which is the motor for the running of the work unit. The purpose of this study was to analyze the influence of work facilities, work placements, and work pressure on performance through work motivation as an intervening variable in the Special Detachment 88 Anti-Terror Unit of the National Police at the National Police Headquarters with a total of 350 personnel. Sampling in this study amounted to 188 samples. In this study, the sampling technique used was proportional sampling using the Slovin formula. The research method uses an associative method with a quantitative approach with analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS Version 4.0 program. The results of this study state that the work facility variable has a positive and significant effect on performance. The work placement variable has a positive and insignificant effect on performance. The work pressure variable has a positive and significant effect on performance. Work motivation variable has a positive and significant effect on performance. The work facility variable has a positive and significant effect on work motivation. The work placement variable has a positive and significant effect on work motivation. The work pressure variable has a positive and insignificant effect on work motivation. Work motivation variable is able to mediate the effect of work facilities on performance. The work motivation variable is able to mediate the effect of work placement on performance. The work motivation variable has not been able to mediate the effect of work pressure on performance. The work pressure variable has a positive and insignificant effect on work motivation. Work motivation variable is able to mediate the effect of work facilities on performance. The work motivation variable is able to mediate the effect of work placement on performance. The work motivation variable has not been able to mediate the effect of work pressure on performance. The work pressure variable has a positive and insignificant effect on work motivation. Work motivation variable is able to mediate the effect of work facilities on performance. The work motivation variable is able to mediate the effect of work placement on performance. The work motivation variable has not been able to mediate the effect of work pressure on performance.